MANAGEMENT AND IMPROVEMENT OF HUMAN RESOURCES ORIENTED TO GLOBAL MARKET COMPETITION: CASE OF INDONESIA ARTIST CERTIFICATION AND PROFESSIONAL STANDARDIZATION POLICY - Pertiwi, Lesli Citra; Yakti, Probo Darono (DIA: Jurnal Administrasi Publik, 2023)
The art ecosystem in Indonesia is colored by two circles: traditional artists and modern artists, where each type of artist has a different interpretation of the process of making works of art. On the one hand, in general, traditional artists prioritize creation, works, and character so that in the process of art, they do not lean towards the economic value of the work produced. Although in many aspects when compared to modern artists, traditional artists lack the appreciation they deserve. In contrast to modern artists, who professionally and access to information become easier to access resources, especially in obtaining funding in the process of creating. These pros and cons are further escalated by the existence of a professionalization policy through an artist certification policy initiated by the Ministry of Education, Culture, Research, and Technology in order to increase competition in the global market. This research started from a research question, namely mapping the problems that arise in the field in the implementation of certification and standardization programs. With qualitative-descriptive methods, this study tries to explore several findings, including: (1) Certification and standardization are urgent as the Indonesian artist community needs to improve its competence in increasing competition on a global scale, regardless of problems in the field to the grassroots, further formulations are still needed; (2) A human resource management approach is taken to regulate artists who have so far been difficult to put in order; and (3) The approach to capacity and quality development is the main motivation of the government in issuing this regulation. This research led to one conclusion, namely the motivation to encourage local art to become a global product facing various challenges, especially in bringing together the interests of artists with the government.